PUTUSAN MAHKAMAH KONSTITUSI TENTANG HAK MENYATAKAN PENDAPAT DPR DAN IMPLIKASINYA TERHADAP PEMAKZULAN PRESIDEN DAN/ATAU WAKIL PRESIDEN - , Hermayanti (Jurnal LEX SPECIALIS, 2010)
AbstractThe existence of the constitutional court which determines the requirements of the exercise stating the number Quarum Parliament from 1 / 4 to 2 / 3 through the decision of a judicial review against Article 184 of Law No. 27 of 2009, has opened the space for the Parliament to be able to use the right declare a previous opinion is very difficult to implemented. the use of this right can lead to the impeachment against the president and vice president if there is no indication in violation of law, so there is the assumption that the more easily use the right opinion, will also simplify the process of Presidential impeachment and / or vice president. in this case can be said that the use of our opinion does not necessarily make it easier on the impeachment, and not solely based on the opinion of the House of Representatives concerning any alleged violation of law, but also must involve the judiciary are the Constitutional Court and the People's Consultative Assembly, and also based upon considerations for the broader interests of the nation